Proteomic analysis of mitochondria from rat liver exposed to chronic fluoride exposure in two experimental periods - Araújo, Tamara Teodoro (2019)
The fluoride ion (F), when ingested in excess, may alter various cellular functions. As liver is an organ of high metabolic activity, it has become the target of investigations on the side effects of F, related to changes in the expression of metabolic proteins, increase in oxidative stress and changes in mitochondrial function. Thus, the objective of the present work was to evaluate the protein expression profile of liver mitochondria from rats chronically exposed to two F concentrations through the drinking water (15 or 50 mgF/L) for 20 or 60 days. Thirty-six liver samples from 21-day-old male Wistar rats were divided into 6 groups (n= 6 animals per group) according to the concentration of F administered in drinking water (0, 15 or 50 mg/L) and the treatment time (20 or 60 days). Mitochondria were extracted from hepatic tissue and prepared for quantitative label-free proteomic analysis (Xevo Q-TOF, Waters). PLGS software was used to detect changes in protein expression among the different groups. Most of the changes were observed in the metabolic pathways such as glycolysis, gluconeogenesis, - oxidation, urea cycle, tricarboxylic acids cycle and electron transport chain, in addition alterations in proteins involved in the antioxidant system, calcium homeostasis and apoptosis. The dose of 15 mgF/L, when administered for 20 days, reduced glycolysis, which was counterbalanced by an increase in other energetic pathways. At 60 days, however, an increase in all energy pathways was observed. On the other hand, the dose of 50 mgF/L, when administered for 20 days, reduced the enzymes involved in all energetic pathways, indicating a lower rate of energy production, with less generation of ROS and consequent reduction of antioxidant enzymes. However, when the 50 mgF/L dose was administered for 60 days, an increase in energy metabolism was seen but in general no changes were observed in the antioxidant enzymes. Except for the group treated with 50 mgF/L for 20 days, all the other groups had alterations in proteins in attempt to maintain calcium homeostasis and avoid apoptosis. Thus, the results suggest that the organism seems to adapt to the effects of F over time, activating pathways to reduce the toxicity of this ion. Ultimately, our findings corroborate the safety of the use of fluoride for caries control.